Multiple Regression Analysis: Self-Efficacy, Self-Regulated Learning, Math Learning Outcomes - Aulia Rahayu; Himmatul 'Ulya; Sintha Sih Dewanti (JNPM (Jurnal Nasional Pendidikan Matematika), 2025)
Learning outcomes are interconnected with the competencies and self-perceptions possessed by each person. This research investigates the impact of self-efficacy and self-regulated learning on the results of mathematics learning. This research included a total of 164 students from two Madrasah Aliyah (MA) located in the Bantul area. The used research methodology is quantitative in nature. The used tools included self-efficacy and self-regulated learning questionnaires, alongside the outcomes of the midterm assessments. Data analysis procedures include doing precondition tests and using multiple linear regression analysis. The prerequisite tests include normality testing, linearity tests, homogeneity tests, and multicollinearity tests. The data processing results in a regression model: , This indicates that self-efficacy and self-regulated learning have a beneficial impact on mathematics learning outcomes. The acquisition of the F test indicates that a significance value of 0.00<0.05 is achieved, indicating that self-efficacy and self-regulated learning have a substantial impact on students' mathematical learning results.